2007
DOI: 10.1177/1049731507300148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Comprehensive Substance Abuse Intervention on Successful Reunification

Abstract: Objective: This study examines permanency outcomes of families with children in foster care who participated in a comprehensive service-delivery program designed to assist families and communities in dealing with alcohol and other drug (AOD) problems. Method: Survival analysis is used to measure the impact of program participation on family reunification and re-entry of children into foster care. Results: The results of this study are that, contrary to initial expectations, participants move more slowly to reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 24 publications
0
38
0
1
Order By: Relevance
“…Three records 580,591,611 were excluded because the focused was on parenting stress and parenting outcomes, rather than child-focused outcomes. Seven records 579,582,589,593,597,606,607 were excluded because participants were not recruited or selected on the basis of their maltreatment; instead they were recruited on the basis of problems including depression, PTSD, substance abuse and delinquency. Three records 585,587,603 were excluded because they focused on general services, such as general foster care and child protection service, and did not focus on a therapeutic intervention for maltreatment.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Three records 580,591,611 were excluded because the focused was on parenting stress and parenting outcomes, rather than child-focused outcomes. Seven records 579,582,589,593,597,606,607 were excluded because participants were not recruited or selected on the basis of their maltreatment; instead they were recruited on the basis of problems including depression, PTSD, substance abuse and delinquency. Three records 585,587,603 were excluded because they focused on general services, such as general foster care and child protection service, and did not focus on a therapeutic intervention for maltreatment.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…However, it also seems likely that parents with more problems would have more difficulty accessing multiple services, and an "everything but the kitchen sink" approach could be problematic. At least one study has found negative associations between receipt of comprehensive intensive services and outcomes of time to reunification and re-entry (Brook & McDonald, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One study articulated service plan requirements and recommended time allotment for a one intensive reunification program treating substance using clients. Requirements included substance abuse treatment services (9 hours per week), employment services (5 hours per week), case management (5 hours per week), parent training (2 hours per week) and other services (domestic violence counseling, family therapy, trauma counseling) (1-4 hours per week), for a total of 22-26 hours per week of service use (Brook & McDonald, 2007).…”
Section: Case Plan Content and Service Targetingmentioning
confidence: 99%
“…Por otro lado, el alcoholismo está mucho más presente entre las familias lusas, especialmente entre los padres. Este es un dato relevante a la hora de analizar las trayectorias y resultados de la intervención, ya que la literatura científica ha identificado el abuso de sustancias por parte de los padres como uno de los factores claves que afectaría negativamente la posibilidad de que se produzca una reunificación familiar (Brook & McDonald, 2007;Fein, 1993;Harris, 1999;Maluccio & Ainsworth, 2003;Mapp & Steinberg, 2007;Smith, 2003;Terling, 1999;Wade et al, 2010).…”
Section: Discusión Y Conclusionesunclassified